Contribuição da certificação do manejo florestal no setor de celulose e papel em relação aos aspectos sociais e ambientais - Batista, Tharcia Ribeiro (2014)
The forest management certification is a system which attests that products are made under rigorous standards and patterns which consider social, economic and environmental aspects. The aim of this research was to verify what Forest Stewardship Council – FSC® principles of forest certification had more frequency of corrective action requests (CARs) and ascertain the tendency of improvement of the sustainability indicators of the companies of the pulp and paper sector. Data were collected from websites, in three stages: i) from the Brazilian Association of Pulp and Paper (BRACELPA), to know the companies of the sector which were certified; ii) from the FSC® , to obtain the certification reports; iii) from the pulp and paper companies, to obtain a historical series of sustainability reports. Four sustainability indicators were analyzed: turnover rate, minimum wage, municipal index of human development and environmental preservation. Principle 4 - Community relations and worker's rights, principle 6 - Environmental impact and principle - Monitoring and assessment 8 were critical for the pulp and paper sector, representing the challenges which were corrected regarding social and environmental aspects. The sustainability indicators, when compared to the Brazilian statistical data, point that the social and environmental aspects had tendency of improvement. It can be stated that the FSC® forest certification influenced the improvement of the social and environmental aspects of the pulp and paper sector, according to the analyzed period, because such aspects showed a growing tendency.